Does Broadband Internet Affect Fertility? - Francesco C. Billari; Osea Giuntella; Luca Stella (Institute of Labor Economics (IZA), 2017)
The spread of high-speed Internet epitomizes the digital revolution, affecting several aspects of our life. Using German panel data, we test whether the availability of broadband Internet influences fertility choices in a low-fertility setting, which is well-known for the difficulty to combine work and family life. We exploit a strategy devised by Falck et al. (2014) to obtain causal estimates of the impact of broadband on fertility. We find positive effects of high-speed Internet availability on the fertility of high-educated women aged 25 and above. Effects are not statistically significant both for men, low-educated women, and under 25. We also show that broadband access significantly increases the share of women reporting teleworking or part-time working. Furthermore, we find positive effects on time spent with children and overall life satisfaction. Our findings are consistent with the hypothesis that high-speed Internet allows high-educated women to conciliate career and motherhood, which may promote fertility with a "digital divide". At the same time, higher access to information on the risks and costs of early pregnancy and childbearing may explain the negative effects on younger adults.
Keywords: J11; J22; 330; Internet; low fertility; work and family; teleworking